2019
DOI: 10.1001/jamaoto.2018.1998
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Duration of Antibiotic Therapy With Major Surgical Site Infection in Cochlear Implantation

Abstract: Infection after cochlear implantation is a rare but serious event that can lead to meningitis. There is no consensus on prevention of infection in these patients, and each center applies its own strategy. OBJECTIVE To describe the rates of major surgical site infection for patients undergoing cochlear implantation who receive prolonged antibiotic treatment compared with those who receive a single perioperative dose of antibiotic prophylaxis. DESIGN, SETTING, AND PARTICIPANTS Retrospective cohort study of patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 32 publications
1
24
1
Order By: Relevance
“…As such, the role of postoperative oral antibiotics in preventing infectious complications is unclear. 7,8…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As such, the role of postoperative oral antibiotics in preventing infectious complications is unclear. 7,8…”
mentioning
confidence: 99%
“…Currently, risk factors that may predispose patients to CI infections are not well understood. As such, the role of postoperative oral antibiotics in preventing infectious complications is unclear 7,8 …”
mentioning
confidence: 99%
“…After title and abstract review, 1945 articles were excluded according to exclusion criteria. A full‐text review was completed on the remaining 179 articles and a total of 38 articles were included for data analysis 4,14–50 . A total of 10 articles met the criteria for meta‐analysis and 28 articles were included for the qualitative systematic review, as they had data regarding wound complications following CI reporting patient‐level factors.…”
Section: Resultsmentioning
confidence: 99%
“…Also discussed is how to perform SAP, whether with a single pre-intervention dose or with a more or less protracted antibiotic administration after surgical wound closure. A recent French study showed that a short treatment is ideal for adults, while a protracted one is more effective in children [57]. However, our panel of experts considered pre-operative antibiotic prophylaxis with a single dose of cefazolin EV as more appropriate, as recommended for clean/contaminated or contaminated ear surgery [49].…”
Section: Scenario #5 Ear Surgerymentioning
confidence: 99%
“…These studies seem to indicate that no form of SAP is useful in modifying the low tendency to develop SSIs in subjects undergoing cochlear implantation, suggesting no use of SAP in these cases [56]. In reality, these data are not convincing, as demonstrated by the fact that some authors believe they should suggest a different choice depending on the characteristics of the individual patient and some prestigious scientific institutions recommend, for caution, a systematic peri-operative prophylaxis with cefazolin EV [57]. Also discussed is how to perform SAP, whether with a single pre-intervention dose or with a more or less protracted antibiotic administration after surgical wound closure.…”
Section: Scenario #5 Ear Surgerymentioning
confidence: 99%